An effective method for percutaneous hemostasis of femoral artery by endovascular balloon occlusion via the occluded dorsal pedalis artery approach in a patient with restricted access site - Hiromi Miwa; Naoki Hayakawa; Yasuyuki Tsuchida; Shinya Ichihara; Satoshi Hirano; Shunsuke Maruta; Kotaro Miyaji; Shunichi Kushida (SAGE Open Medical Case Reports)
Hemostasis of a large-diameter sheath is sometimes problematic, especially for patients with limited approach sites. Here, we describe an effective and safe endovascular method for hemostasis of the femoral artery via the dorsalis pedis artery. The patient was a 75-year-old man who was performing endovascular therapy via the left common femoral artery. A pseudoaneurysm developed, and it was treated via the right common femoral artery. He developed acute coronary syndrome 1 week later, and an intra-aortic balloon pump therapy was inserted via the right femoral artery. Neither radial artery was available, and the right brachial artery was punctured to perform coronary revascularization. When the intra-aortic balloon pump was to be removed, the right dorsal pedis artery was punctured, and hemostasis was achieved without any complications. We conclude that the trans-ankle intervention may be an effective and less invasive technique for percutaneous hemostatic procedures.